Analisis Tingkat Pengetahuan Mahasiswa Kepaniteraan Terhadap Tatalaksana Avulsi Gigi Permanen - Zherina Ade Afrilia; M. Fajrin Wijaya; Ardian Jayakusuma Amran; Lukman Bima; Nur Asmah (PPNI UNIMMAN, 2023)
Human knowledge comes from education, experience and social interaction. Clerkship students actively participate in clinical training under supervision. Maxillofacial trauma, often caused by accidents, can cause mandibular fractures. Tooth avulsion, detachment from the socket due to injury, often occurs in the maxillary central incisors. Immediate tooth replantation is the best treatment. Research Objective: To determine the level of knowledge of clerkship students regarding the management of permanent tooth avulsions. Method: This research uses an analytical observational research design with a cross sectional research design. The population in this study were all clerkship students in 2023 with a total of 88 respondents. Determining the number of samples uses total sampling. Data collection used a knowledge level pattern questionnaire. Data analysis used SPSS with Mann Whitney and Kruskal-Wallis statistical tests. Research Results: Most of the respondents were women, 72 respondents (84.7%). Most of the respondents had a clerkship period of less than 1 year, 43 respondents (5.6%). Most of the respondents had undergone oral surgery, 50 respondents (58.8%). Most respondents had knowledge in the low category, 38 respondents (44.7%). Conclusion: The majority of students have a low level of knowledge regarding the management of permanent tooth avulsion. There was no significant difference between knowledge regarding the management of permanent tooth avulsion. Suggestion: Efforts are needed to increase students' level of knowledge regarding the management of permanent tooth avulsions.